South African management literature over the past fifteen years: Content analysis of the three top South African management journals - E. Botha; N. Lilford; L. Pitt (South African Journal of Business Management, 2011)
This article analysed 15 years, from 1996 to 2010, of research published in the three leading South African business management journals. The three journals chosen were the South African Journal of Business Management, the South African Journal of Economic and Management Sciences and Management Dynamics. Content analysis was used to compare five broad themes in the journals: firstly the nature of authorship was examined, and then the most published as well as most prolific authors were identified. Thirdly, the most prominent universities and departments were identified whereafter the research themes and disciplines of the articles and authors were analysed. Lastly, various manuscript characteristics were investigated. This article provides a clear picture of the evolution of South African management literature over the past fifteen years.
Keywords: 650